Role of Cardiac Troponin I Level in Predicting in Hospital Outcomes in Patients with ST-segment Elevation Myocardial Infarction in Erbil-Iraq - Zangana, Salam Naser; AL-Othman, Abdul kareem A; AL-Tawil, Namir G (Diyala Journal of Medicine, 2018)
Background: The correlation of cardiac troponin I with early in-hospital outcomes in acute myocardial infarction is not well established. Objective: To assess the role of troponin I in predicting in-hospital outcomes and early left ventricular systolic dysfunction in patients with ST-segment elevation myocardial infarction. Patients and Methods: A prospective study which consist of 116 patients (74 were males and 42 were females), with ST-segment elevation myocardial infarction who had been admitted to the Coronary Care Unit from March 2015 to September 2015 were enrolled. Patients were divided according to the level of troponin I on admission into 3 groups (low, medium and high elevation). Results: The mean age (+ SD) of the patients was 60+11.4 years. The troponin level of 66.2% of males was high compared with 52.4% of females (p=0.002). The incidence of acute pulmonary edema (21.1%), cardiogenic shock (7%) and early left ventricular systolic dysfunction (49.3%) was significantly higher among patients with high troponin level compared with (0%, 0% and 16%, respectively) among patients with low troponin level. All deaths and cardiac arrest were of high troponin level. Conclusion: High admission troponin I in ST-segment elevation myocardial infarction permits early identification of patients at increased risk of major cardiac complications and death.